Graphene reinforced biodegradable poly(3-hydroxybutyrate-co-4-hydroxybutyrate) nano-composites - V. Sridhar; H. Park; I. Lee; H. H. Chun (eXPRESS Polymer Letters)
Novel biodegradable poly(3-hydroxybutyrate-co-4-hydroxybutyrate) [PHBV]/graphene nanocomposites were prepared by solution casting. The thermal properties, crystallization behavior, microstructure, and fracture morphology of the composites were investigated. Scanning electron microscope (SEM) results show that graphene layers are homogeneously dispersed in the polymer matrix. X-ray diffraction (XRD) and dynamic scanning calorimetry (DSC) studies show that the well dispersed graphene sheets act as nucleating agent for crystallization. Consequently, the mechanical properties of the composites have been substantially improved as evident from dynamic mechanical and static tensile tests. Differential thermal analysis (DTA) showed an increase in temperature of maximum degradation. Soil degradation tests of PHBV/graphene nanocomposites showed that presence of graphene doesn’t interfere in its biodegradability.